An Examination of Psychological Resilience and Remembered Parental Care among University Students - Ozgur Demirci Seyrek; Ercümend Ersanlı (Journal of Educational Issues, 2024)
In this study, the aim was to examine the relationship between the psychological resilience and remembered parental care of college students in young adulthood and whether this relationship varies according to gender and perceived socio-economic level. A correlational model was used as a research model. For data collection purposes, ‘‘a personal information form,’’ the “Psychological Resilience Scale for Adults” and the “Parental Bonding Instrument” were used by the researchers. The age range of individuals involved in the study ranged from 18 to 26. The research results were tested with SPSS 21. A strong positive relationship was found between remembered mother and remembered father care, while a moderately positive relationship was found between psychological resilience and remembered mother and father care. One of the findings is that there was a significant difference between the care of mothers and of fathers as remembered by male and by female participants. In addition, the study found that there was a statistically significant difference in the level of remembered maternal care, remembered paternal care, and psychological resilience in terms of perceived socioeconomic level. Based on these results, it can be argued that perceived socioeconomic status, which refers to the perception of the presence of means one possesses, had an impact on the individual’s psychological resilience in a direct proportion. In line with the findings, the significant correlation between remembered mother’s care and remembered father’s care can be shown as a long-term contribution to the positive effect on children of the rapport between mother and father. Alongside the fact that the remembered mother’s and father’s care was an important variable in predicting the factors that affected the psychological resilience of undergraduates, it is noted that democratic, caring and warm paternal attitudes are important, rather than the traditional sex-oriented attitudes. Hence, one can argue that it is of importance that fathers and fathers-to-be have increased awareness of their roles in the long-term development of psychologically resilient youngsters, by means of taking on more responsibilities in childrearing.